2007
DOI: 10.1111/j.1447-0594.2007.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones as Putative Anti‐aging Food Factors in Asia and Effects of Isoflavone Aglycone‐rich Fermented Soybeans on Bone and Glucose Metabolisms in Post‐menopausal Women

Abstract: Objective: Since soy isoflavone intake, high in Japanese and Asian populations was epidemiologically associated with lower risks of cardiovascular diseases(CVD), we focused on soy isoflavone effects on other risks of lifestyle-related diseases and investigated whether or not the intake of isoflavone aglycone-rich fermented soybeans affected bone and glucose metabolisms in post-menopausal women.Methods: Healthy post-menopausal women aged 47 to 70 years, 65 in total, were invited to a test diet-placebo independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Beyond definitions based on technology or outcomes, biomarkers can also be classified based on their intended use. For instance, food intake biomarkers (FIBs) can be used to assess the intake of a specific food with a distinct dose-and time-dependent response, while effect biomarkers can help indicate a physiological or health state following the exposure to a food or diet (109). FIBs can also be used to monitor compliance to interventions in clinical trials (110), and may provide valuable information beyond self-reported intake particularly when food composition data are not available or limited.…”
Section: Food Intake Biomarkers As Objective Measures Of Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond definitions based on technology or outcomes, biomarkers can also be classified based on their intended use. For instance, food intake biomarkers (FIBs) can be used to assess the intake of a specific food with a distinct dose-and time-dependent response, while effect biomarkers can help indicate a physiological or health state following the exposure to a food or diet (109). FIBs can also be used to monitor compliance to interventions in clinical trials (110), and may provide valuable information beyond self-reported intake particularly when food composition data are not available or limited.…”
Section: Food Intake Biomarkers As Objective Measures Of Intakementioning
confidence: 99%
“…Analysis of several fermented soy products, including Chungkookjang, tempeh, doenjang, and miso, revealed higher levels of isoflavones (genistin, daidzin, glycitin, genstein, daidzein) and/or amino acids (in particular glutamate) compared to unfermented soybean (105). In addition to soy isoflavones and aglycones, vitamins B2 and B12, and gamma aminobutyric acid (GABA), are increased in fermented soy products (106), and a variety of bioactive peptides have been identified, such as F2-2-2 and Fr-2-3 in chungkujang, Arginine-Proline in doenjang, Phenylalanine-Isoleucine-Glycine (1:2:5) in dou-chi, and Valine-Proline-Proline and Isoleucine-Proline-Proline in miso paste containing casein (107)(108)(109). While many of these compounds are present across other foods as well (e.g., vitamin B12), which limits their usefulness as FIBs for fermented soy intake, their combination in a multi-marker approach warrants investigation.…”
Section: E) Fermented Legumes and Soymentioning
confidence: 99%